(untitled) (Law, State and Telecommunications Review, 2014)
Purpose ”“ This study tackles the right to self-determination regarding information flows from its historical perspective. Methodology/approach/design ”“ With that in mind, this work aims to be a consolidation of fundamental rights’ history, from their predominantly individualist, bourgeois, liberal inception, to the moment when they turned to values ”‹”‹that transcend the individual, focused on social interaction and joint realization of human dignity. This analysis addresses the right to privacy as a guiding line by evidencing the changes caused by the intensive adoption of communication technologies Findings ”“ The right to privacy nowadays presents itself with a striking social dimension. Paying attention to that aspect paves the way to its use as an important tool for ensuring the enforcement of the right to privacy in the new scenario of technological achievements and increasing of personal data flow. Practical implications ”“ Such analysis shows that the effective implementation of these rights requires integrated analysis of what was once considered in a fragmented way.